Geochemistry of Groundwater in the Uva Province, Sri Lanka—Implications for Chronic Kidney Disease of Uncertain Origin - Piyathilake, I. D. U. H.; Udeshani, W. A. C.; Hapuarachchi, H. A. C. S.; Ranaweera, L. V.; Udayakumara, E. P. N.; Gunatilake, S. K.; Dissanayake, Chandra B. (Frontiers in Water, 2021)
The prevalence of Chronic Kidney Disease of uncertain etiology (CKDu) in the Uva Province (UP) of Sri Lanka has received much attention over the last two decades. Many scientists assumed that prolonged consumption of drinking water with high levels of contaminants may be the causative factor. Thus the prime objective of this study is to develop a binary logistic regression model based on water quality parameters and the prevalence of CKDu to find out the geochemical risk factors that affect the CKDu. For this, 260 groundwater samples were collected following stratified random sampling method and analyzed for its major cations, anions, and selected trace element contents. According to the best-fit model, F- and PO43- levels of the groundwater were found to be the geochemical risk factors that were significantly associated with the progression of CKDu in the study area. Furthermore, it was shown that geochemical processes such as dissolution of bedrocks are the causative phenomenon of the enhancement of F- levels in the groundwater sources. It has also been observed that the PO43- concentrations of the groundwater possibly increase due to the intensive application of agrochemicals in addition to geogenic sources. The results of this study can be used by the government authorities in groundwater management and in the management of the prevalence of CKDu disease in the study area. Furthermore, the findings of this study will contribute to the policymakers in Sri Lanka for providing safe drinking water to meet the sustainable development goals.